2015
DOI: 10.1007/s40030-015-0115-1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies on Behaviour of Reinforced Geopolymer Concrete Beams Subjected to Monotonic Static Loading

Abstract: This work describes the experimental investigation on behaviour of reinforced GPC beams subjected to monotonic static loading. The overall dimensions of the GPC beams are 250 mm 9 300 mm 9 2200 mm. The effective span of beam is 1600 mm. The beams have been designed to be critical in shear as per IS:456 provisions. The specimens were produced from a mix incorporating fly ash and ground granulated blast furnace slag, which was designed for a compressive strength of 40 MPa at 28 days. The reinforced concrete spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Highly alkaline liquids dissolve silicon and aluminum atoms in the source materials and form the geopolymeric binder. Efficiency in the production of geopolymer concrete is highly dependent on the types of aluminosilicate sources and activators [5,6]. The raw material used as a source, alkaline solution concentrations, and curing conditions play an essential role in increasing the strength of geopolymer concrete by improving the polymerization process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly alkaline liquids dissolve silicon and aluminum atoms in the source materials and form the geopolymeric binder. Efficiency in the production of geopolymer concrete is highly dependent on the types of aluminosilicate sources and activators [5,6]. The raw material used as a source, alkaline solution concentrations, and curing conditions play an essential role in increasing the strength of geopolymer concrete by improving the polymerization process.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of reinforcement ratio on geopolymer concrete beams in terms of bending capacity and ductility was similar to conventional reinforced concrete beams. In parallel studies, it has been reported that the flexural behavior of fly ash-based geopolymer concrete beams is identical to traditional reinforced concrete beams, such as initial cracking load, crack width, load-deflection relationship, bending stiffness, ultimate load, and failure mode [19][20][21][22][23][24][25][26][27]. The bending behaviors of geopolymer-reinforced and cementitious reinforced concrete beams were investigated by numerical analysis (ANSYS APDL) and confirmed by experimental studies.…”
Section: Introductionmentioning
confidence: 99%
“…The production of geopolymer concrete is by reacting an alkaline liquid with a source material rich in silica and alumina such as slag, fly ash, red mud, and silica fume. Geopolymer binder is used in many phases as an example; paste, mortar, and concrete in many investigations [18][19][20][21][22]. The most crucial feature of geopolymer concrete as new material is its high resistance to aggressive media attacks.…”
Section: Introductionmentioning
confidence: 99%
“…By applying splitting, shear, significant cracking, and conical type failure tests on geopolymer mortar specimens, the geopolymer mortar specimens can be classified as brittle material [19]. Comparing geopolymer concrete to ordinary cement concrete in the case of precast units, geopolymer concrete is more environmentally friendly and economical than ordinary cement concrete [20].…”
Section: Introductionmentioning
confidence: 99%
“…And concluded that load deflection features of GPC and OPC beams are same, observed that ultimate moment resistance capacity is more in case of GPC beams than that of OPC beams [9]. C. K. Madheswaran et al had conducted the experimental investigations on OPCC and GPC beams with varying of shear span to depth ratios of 1.5 and 2 ,with differing proportions of solutions in GPC mixes and concluded that load deflection behaviour is similar in case of GPC and OPC beams, there was a good compatibility between experimental analytically predicted values of deflection [10]. D. Annapurna et al had described the experimental work and analytical modelling using FEM analysis in ANSYS software to simulate the behaviour of GPC beams subjected to flexure and concluded that at various stages of cracking overestimates the deflection by 6% to 14% so, which enables to use the theoretical model to predict deflections [11].…”
mentioning
confidence: 99%